IMPLEMENTATION OF COOPERATIVE LEARNING MODEL NUMBERED HEADS TOGETHER STRUCTURAL APPROACH TO IMPROVE MATHEMATICAL LEARNING OUTCOMES IN CLASS VIII.3 MTs MUHAMMADIYAH 02 PEKANBARU - Chindy Julia Fitrah; Syofni; Nahor Murani Hutapea (Jurnal Prinsip Pendidikan Matematika, 2020)
This study aims to improve the learning process and increase the students’ mathematics learning outcomes through the implementation of the Cooperative Learning Numbered Heads Together Structural Approach. The subjects of this study were 36 students consisting of 21 male students and 15 female students. The study was conducted in the odd semester of the academic year 2019/2020. This research is Classroom Action Research with two cycles and each cycle has four stages: planning, implementation, observation, and reflection. The research instruments consist of learning instruments and data collector instruments. The learning instruments used are Syllabus, Lesson Plans, Student Activity Sheets, and the NHT question sheet. The data collector instruments are the observation sheets and math achievement tests. The observation sheet was analyzed descriptive qualitative while the test of mathematics learning outcomes was analyzed statistically. Based on descriptive qualitative analysis was obtained that implementation of the learning process on cycle II better than cycle I. The study result indicated that the implementation of the Cooperative learning model of the Numbered Heads Together Structural Approach can improve the learning process and improve mathematics learning outcomes of class VIII.3 student of MTs Muhammadiyah 02 Pekanbaru.